2000
DOI: 10.1159/000017451
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Expression of the GLUT4 Glucose Transporter in the Mouse

Abstract: The GLUT4 glucose transporter is primarily expressed in skeletal muscle, heart and adipose tissue, where its expression is postnatal, coincident with the acquisition of insulin-regulated glucose transport. In muscle, contraction also regulates GLUT4 activity in the postnatal animal. Here we demonstrate that GLUT4 is expressed in the developing mouse embryo with specific tissue and spatiotemporal patterns. From embryonic day 9 (E9; E1 = day of copulation plug) to postnatal day 70 (P70), mice were analyzed for G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
1
20
0
1
Order By: Relevance
“…Additionally, higher rates of insulin infusion and higher plasma insulin concentrations might increase production of and/or translocation of other glucose transporter isoforms, including GLUT1, which our previous studies did show was responsive to insulin with increased expression and abundance, and GLUT3, which has been found in fetal skeletal muscle (6,14,29,(33)(34)(35)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, higher rates of insulin infusion and higher plasma insulin concentrations might increase production of and/or translocation of other glucose transporter isoforms, including GLUT1, which our previous studies did show was responsive to insulin with increased expression and abundance, and GLUT3, which has been found in fetal skeletal muscle (6,14,29,(33)(34)(35)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 91%
“…We and others have previously shown that Glut4 is also expressed in chondrocytic populated growth centers (27,38,61). Glut4 may be more important in pre-and postnatal bone development than in adult life (60). This may contribute to intrauterine growth retardation, which is associated with insulin resistance (8,9,39).…”
Section: Discussionmentioning
confidence: 97%
“…Recent data have shown that GLUT4 and GLUT8 are expressed in the developing mammalian brain and that their expression is modulated throughout the fetal to adult stages (42)(43)(44)(45). GLUT4 is present in the embryo brain as early as embryonic day 9 (E9) and E14 in rats, and the expression level peaks at E14 and is lower at E19 and remains stable thereafter up to adulthood (42,43).…”
Section: Cellular Features Of Glut4 and Glut8 In The Brainmentioning
confidence: 99%